Activity-Based Therapy in a Community Setting for Independence, Mobility, and Sitting Balance for People With Spinal Cord Injuries. (April 2019) - de Oliveira, Camila Quel; Middleton, James W; Refshauge, Kathryn; Davis, Glen M
Introduction: Activity-based therapy (ABT) aims to activate the neuromuscular system below the level of the spinal cord lesion and promote recovery of motor tasks through spinal reorganisation, motor learning and changes to muscles and sensory system. We investigated the effects of a multimodal ABT program on mobility, independence and sitting balance in individuals with spinal cord injury (SCI). Methods: Retrospective clinical data from 91 adults who independently enrolled in four community-based ABT centres in Australia were analysed. The multimodal ABT program was delivered for 3 to 12 months, one to four times per week. Assessments were undertaken every 3 months and included the Modified Rivermead Mobility Index (MRMI), Spinal Cord Independence Measure (SCIM) and seated reach distance (SRD). A linear mixed model analysis was used to determine time-based and other predictors of change. Results: There was a significant improvement after 12 months for all outcome measures, with a mean change score of 4 points in the SCIM (95% confidence interval [CI]: 2.7-5.3, d = 0.19), 2 points in the MRMI (95% CI: 1-2.3, d = 0.19) and 0.2 in the SRD (95% CI: 0.1-2.2, d = 0.52). Greater improvements occurred in the first 3 months of intervention. There were no interaction effects between time and the neurological level of injury, American Spinal Injury Association Impairment Scale classification, or duration post-injury for most outcomes. Conclusions: A community-based ABT exercise program for people with SCI can lead to small improvements in mobility, independence and balance in sitting, with greater improvements occurring early during intervention.